Alienation form for ornament’s clouds in Quran (Al-Academy, 2017)
This research attend about Alienation form for ornament’s clouds in Quran, which includes four parts, the first part talks about the research problem, the researcher identified by following question :( what’s the Alienation form for ornament’s clouds in Quran?). And then the research importance. The research goal talks about Alienation form for ornament’s clouds in Quran. And also research borders, likes means objectives borders, places borders, As well as Terms Definitions, in second part talks about Theoretical framework and previous studies, includes two parts, the first one study Alienation form, meaning and understandable, the second one talks about Alienation form in Islamic arts, As well as the researcher find only one study has relation with this study, after that’s his foxing for Theoretical framework Indicators , the third part of this study talks about (research procedures), and then rely to Descriptive analytical method to analysis The samples, (4) (50%) Of the total (8) samples according to goal of research. Then find some Results Including:1- The Alienation form can found it in the movement of snack like (1, 4) (50%), this type of cloud is characterized by giving manifestation physically and aesthetically distinct.2- The Alienation form lobular Heart pinned like form (1, 2, 3) (75%).this type used for Repetition property.3- The ornament’s cloud makes inverse rotation Organize like (S) letter in English (3) (25%).4-The ornament’s cloud makes Free regulation (1, 3) (50%). This Organize has Diversity design, because Get rid of the monotony, to give the ornament’s clouds Exciting and attract the attention.The Conclusions Including:1- Employ the decorative for floral decorations Design, to add new decorative Reflect Functional and aesthetic results.2- The Alienation form gives many design options to make good forms Compatible with Core Area. After the Conclusions, the researcher talks about Recommendations and suggestions